"Look at Me:" Portraiture and Agency - Sauer, Janet S. (Disability Studies Quarterly, 2012)
Keywords: disability, methodology, portraiture, social justice, special education Historically, the dominant research paradigms involving the study of people with disabilities involved experimentally designed studies or other medically orientated approaches. This paper examines portraiture as a form of qualitative inquiry offering emancipatory possibilities for children with significant disabilities and transformative positive reinterpretations of disability as a social construct for their teachers and other people in their lives. Three narrative portraits of young people with disabilities were created based on a year-long portraiture study involving the collection of observational data, informal interviews, artifacts, and discourse analysis to capture the “essence” of their humanness. Through an examination of this portrait study and others from across the humanities, this paper provides examples where the “subjects” asserted themselves in ways akin to Giroux’s agency (1987) suggesting portraiture might provide a unique and credible avenue to respectfully study and learn more about people with disabilities too often left on the fringe of society.